CRITICAL STUDY OF CRIMINAL SANCTIONS FOR CHILD NEGLECT BY PARENTS IN INDONESIA - Syahrin, M. Alpi (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
Cases of child neglect are considered an indicator of the minimal quality of child protection in Indonesia. The law that is needed is criminal law because it is considered effective. Sanctions for perpetrators of criminal acts of child neglect are explained in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Criminal Provisions, Article 77B "Any person who violates the provisions as intended in Article 76B ("Every person is prohibited from placing, allowing, involving, ordering to involve a child in a situation of abuse and neglect"), shall be punished with a maximum imprisonment of 5 (five) years and/or a maximum fine of IDR 100,000,000.00 (one hundred million rupiah)”, however the fact is that sanctions against parents who do not support their children as per the court decision regarding the obligation to pay child support, especially for a father, are almost never implemented because of the umbrella There is no specific law that provides sanctions for fathers who do not support their children. Therefore, in order to increase the effectiveness of implementing child protection, it is necessary to provide criminal sanctions for child neglect committed by parents, especially for fathers who do not carry out their obligations, namely by revising the Elucidation to Article 76 B of Law Number 35 of 2014 concerning Child Protection, with the addition of an editorial explaining the article, "what is meant by Neglect, includes the Parent's (Father's) Denial of Payment of Child Support based on a Religious Court Decision which has permanent legal force.